1991
DOI: 10.1002/ajp.1350240315
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time ultrasonography as a clinical and management tool to monitor pregnancy in a chimpanzee breeding colony

Abstract: Accurate assessment of gestational age, date of parturition, and evaluation of placental abnormalities are essential to monitor obstetrical and fetal complications in captive chimpanzee (Pan troglodytes) breeding colonies. Since ultrasonography is a safe and noninvasive technique for monitoring chimpanzee pregnancies, we have developed a technique to estimate the date of parturition using the fetal biparietal diameter (BPD) of the skull from real-time ultrasonographic measurements. A formula for determining ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…Interestingly, the shift observed between the curve drawn by Lee and by the authors may be explained by a different gestation length (240 days for Lee, 229 days for CIRMF). As our data are in accordance with those already published, BPD seems to be a good index of gestational age in chimpanzees, as in humans and baboons [9]. However, because of the flattening of the curve and the wider dispersion of values toward the end of pregnancy, BPD seems less predictive at the end than at the beginning of pregnancy [2].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Interestingly, the shift observed between the curve drawn by Lee and by the authors may be explained by a different gestation length (240 days for Lee, 229 days for CIRMF). As our data are in accordance with those already published, BPD seems to be a good index of gestational age in chimpanzees, as in humans and baboons [9]. However, because of the flattening of the curve and the wider dispersion of values toward the end of pregnancy, BPD seems less predictive at the end than at the beginning of pregnancy [2].…”
Section: Discussionsupporting
confidence: 92%
“…However, the human curve has a steeper slope and clearly diverges from the chimpanzee and gorilla curves after 20 weeks of pregnancy. Struthers et al [16] and Lee et al [9] reported a linear increase in BPD in chimpanzees, while we obtained a polynomial curve. Also, the curve reported by Lee seemed slightly shifted relative to ours, while that of Struthers was almost entirely superposable (Fig.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Because these features have a fundamental role in resisting shear force 14 , similar patterns of lumbar dimorphism in Australopithecus and Homo indicate that spinal shear was also a major challenge in australopiths in general, and especially for gravid females. Similarities in body size and life history between australopiths and chimpanzees suggest that term mass and duration of gestation for australopiths was chimpanzee-like (1,590 g at 230 days) 17,18 rather than human-like (3,200 g at 290 days) 19,20 . Even so, term mass of the australopithecine fetus would easily have exceeded the 40% load trigger of 1,200 g in human pregnancy for a substantial period of pregnancy, approximately the last trimester (Supplementary Information).…”
Section: Fetal Load and The Evolution Of Lumbar Lordosis In Bipedal Hmentioning
confidence: 97%